Analisis Bibliometrik Terhadap Penggunaan Information and Communication Technology (ICT) Pada Pembelajaran Matematika - Julianis, Juli; Zulfah; Astuti (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
The use of ICT in learning mathematics can help students to understand mathematics lessons easier. This study aims to determine the trend of articles using ICT in mathematics learning, the trend of articles that have the highest number of citations, classification of journal rankings, country of journals, and mapping in finding trends in international scientific publications with the Scopus database. The method used is bibliometric analysis. The population of this study was 200 articles as a result of searching data using the Publish or Perish (PoP) application from 2011-2021, obtained 92 articles as a sample that match the keyword criteria. Data is stored in Microsoft Excel as data processing material and stored in RIS format for use in VOSviewer software to get a mapping in finding publication trend. The trend of articles on the use of ICT has increased significantly from 2017 to its peak in 2019. The mapping analysis of the VOSViewer software has three themes related to the use of ICT in mathematics learning, namely “memory aid”, “effectiveness”, and “grade” which are still rarely studied and become the latest themes in research. This theme can be an opportunity for further research.